Front Cover: Near‐Infrared Light Responsive Imaging‐Guided Photothermal and Photodynamic Synergistic Therapy Nanoplatform Based on Carbon Nanohorns for Efficient Cancer Treatment (Chem. Eur. J. 49/2018). Issue 49 (10th August 2018) - Gao, Cunji; Dong, Pei; Lin, Zhaoxing; Guo, Xiaolu; Jiang, Bang‐Ping; Ji, Shichen; Liang, Hong; Shen, Xing‐Can
Abstract : Indocyanine green (ICG) is an effective light absorber for laser‐mediated photodynamic therapy. However, applications of ICG have been limited due to its fast degradation and poor photostability in water. Herein, a multifunctional nanoplatform was developed by coating ICG on the surface of single‐walled carbon nanohorns (SWNHs) via π–π stacking. The obtained SWNH‐ICGs exhibit highly efficient thermal/photoacoustic (PA) imaging‐guided photothermal therapy (PTT) and photodynamic therapy (PDT) effects even under low‐power laser irradiation. More information can be found in the Full Paper by X.‐C. Shen et al. onpage 12827 .